Effects of transformations in the urban structure on the quality of life of city residents in the context of recreation - Hrehorowicz-Gaber, Hanna (Bulletin of Geography. Socio-economic Series, 2013)
Accumulating over time, spatial transformations in Kraków have been changing the city’s structure. The contemporary image of the city is creating a new model of life and has a major effect on the functional and spatial conditions for its residents. Life in the city is dictated by the rhythm of daily routines, and the time of leisure has been reduced to a minimum. Less and less frequently are public and semi-private urban spaces used in the traditional manner and their number is decreasing. A considerable role in the decrease in the space for relaxation in the city is played by the purchasing power of money which is winning for itself the space for new residential estates. The disappearance of green areas can be best illustrated by the example of the green areas between Kraków and Nowa Huta. Historically, Nowa Huta was set up as an organism separate from Kraków. In 1956, Anna Ptaszycka presented a new plan for Kraków spatial development which curbed industrialisation and promoted Howard’s ideas of garden cities. In 1966, the largest park in that area was established, its basic function was to isolate Kraków from Nowa Huta and the steel plant there. As a result of the projects developed in recent years, the compact greenery is smaller, and more and more areas are being taken over for various projects. Spontaneous development of Kraków, without any master plans, for some small parts of city structure, is a huge threat to the preservation of existing leisure areas. Because of this, precise guidelines are needed for the intended use of areas neighbouring environmentally sensitive grounds, defining their type, scale and impact, in order to protect the landscape attractions which are amongst the desired recreational characteristics.